Larval Exposure to Chlorpyrifos Affects Nutritional Physiology and Induces Genotoxicity in Silkworm Philosamia ricini (Lepidoptera: Saturniidae) - Kalita, Moni K.; Haloi, Kishor; Devi, Dipali (Frontiers in Physiology, 2016)
Chlorpyrifos is a most widely used organophosphate insecticide because of its cost effectiveness and degradable nature. However, this pesticide enters and contaminates the environment either by direct application, spray drifts or crop run off and shows adverse effect on the non-targeted organisms. Philosamia ricini (eri silkworm), one of the most exploited, domesticated and commercialized non mulberry silkworm is known for mass production of eri silk. The silkworm larvae get exposed to pesticide residues on the leaves of food plants. The present study investigates the effect of commercial formulation of chlorpyrifos (Pyrifos-20 EC) on eri silkworm. Initially the LC50 value of chlorpyrifos was determined at 24 - 96 h and further experiments were carried out with sub lethal concentrations of the chlorpyrifos after 24 h of exposure period. The potential toxicity of chlorpyrifos was evaluated as a fuction of metabolism and nutritional physiology in 3rd, 4th and 5th instar larvae. Alteration in histoarchitecture of 5th instar eri silkworm gut exposed to sub lethal concentration of chlorpyrifos formulation was also studied. Chlorpyrifos induced genotoxicity in silkworm hemocytes was also investigated by single cell gel electrophoresis, micronuclei assay and apoptosis assay. Herein, LC50 values of chlorpyrifos were calculated as 3.83, 3.35, 2.68 and 2.35 mg/L at 24 h, 48 h, 72 h and 96 h respectively. A significant decrease in trehalose activity along with digestive enzyme activity was observed in chlorpyrifos affected groups (P < 0.05). Further, genotoxicity study revealed higher tail percentage, tail length and tail moment of the damage DNA in chlorpyrifos exposed groups (P < 0.001). Moreover, at 2.0 mg/L concentration, 10 fold increases in tail length was observed as compared to the control. Results showed activation of caspase activity following 24 hr chlorpyrifos exposure (1.5 mg/L and 2.0 mg/L) in a dose-dependent manner. Moreover, in control group less number of apoptotic cells was detected, however in both chlorpyrifos exposed groups number of apoptotic cells were more. Taken together, this study provides evidence that chlorpyrifos pollution might have adverse effect on overall nutritional physiology and genotoxicity of eri silkworm that could lead to reduced survivability of this economically beneficial